The Effects of Longer School Days on Mothers' Labor Force Participation - Matias Berthelon; Diana Kruger; Melanie Oyarzún (Institute for the Study of Labor (IZA), 2015)
Lack of adequate childcare is a main reason women cite for not participating in the labor force. We investigate the effect of a reform that lengthened school schedules from half to full days in Chile essentially providing zero-cost childcare on different maternal labor participation outcomes. We identify the effect of the policy from its implementation across municipalities over time and rule out alternative explanations, finding evidence of positive and important effects on participation and more permanent attachment to the labor force. Additionally, we also find results are driven by the provision of full day schooling in 1st and 2nd grades.
Keywords: H4; J2; J4; I2; 330; full day schooling; primary education; female labor participation; education reform; Chile